(untitled) (Swiss Medical Weekly, 2015)
INTRODUCTION: Methotrexate is used to treat many medical conditions with medication schedules that differ widely in dosage and frequency. The high potential of erroneous too frequent low-dose methotrexate prescriptions leading to severe adverse reactions is well known; however, documentation is mainly limited to case reports. We reviewed all methotrexate prescriptions in a secondary and a tertiary care hospital to analyse the incidence of too frequent low-dose methotrexate prescriptions, and assessed the quality assurance concepts implemented. METHODS: All nononcological low-dose methotrexate prescriptions issued for inpatients within 55 months were analysed to identify too frequent prescriptions potentially leading to harmful overdosing. Subsequently, clinical pharmacologists reviewed all new methotrexate prescriptions with resulting interventions at the physician level in the tertiary care hospital. The impact of an interruptive alert displayed at methotrexate order entry was assessed in the secondary care hospital. RESULTS: The incidence of too frequent prescriptions at the tertiary hospital was 1.6% (five medication errors and nine near misses in 888 inpatients). After introducing checks by pharmacologists, two prescription errors were intercepted during the 8 month quality assurance period. At the secondary care hospital the incidence dropped from 2.5% (2/79, 20 months) to 0.8% (1/123, 35 months) after the alert was implemented. CONCLUSIONS: The incidences of erroneous too frequent low-dose methotrexate prescriptions observed at both hospitals were considered too high due to the high potential for increased morbidity, mortality and costs. Therefore, quality assurance measures were implemented and the preliminary data show a positive impact on patient safety for both approaches.